All‐Metal Oxide Transparent Photovoltaic for High‐Speed Binary UV Communication Window (Adv. Electron. Mater. 9/2021). (9th September 2021) - Patel, Malkeshkumar; Bhatnagar, Priyanka; Bist, Shristi; Kim, Joondong
Abstract : Transparent Photovoltaic Systems Signals can be invisibly transmitted in platform of transparent photovoltaic systems. Light‐coded information of 'P‐E‐D‐A‐L' is translated as wording of 'PEDAL' through an optical communication window. Joondong Kim and colleagues demonstrate a self‐power‐supporting messenger with alltransparent concept in article number 2100478 . One day, high‐secure optical communication will work invisibly and powerlessly.